Business Strategies in Improving Competitive Advantage in The New Normal - Ni Made Suartini (Enrichment : Journal of Management, 2021)
The new normal changes the way businesses interact. Businesses are required to survive and compete while complying with the health protocols. This study aimed to determine the right company strategy in accordance with the internal conditions of the company and the business industry in increasing competitive advantage during the new normal. Data were analyzed using descriptive qualitative methods. The results of the study: 1) The functional analysis of Desa House Villa and Homestay Seminyak, and the Fashion Hotel Legian seen from the function of the company has been going well. 2) With regard to the analysis of the industrial environment, the company has many competitors. The threat of newcomers is relatively high because it is easy to obtain business permits. Substitution products affect the continuity of the company's business, overcome by differentiating services and making homestays. There are many suppliers but the market available is few. Customer characteristics prioritize quality, service and price. Price adjustments are made to get around the characteristics of the guests. The conclusion of this study: the business strategy applied is Porter's Generic strategy, namely differentiation of services and products to be different from competitors and have benefits for customers, differentiation of locations, prices and strategies to focus on certain markets targeting guests staying with MICE facilities. It is suggested that sinergy is requires between the company's functional environment and competition in the industrial environment that is happening in increasing the competitive advantage of the two companies.